Relationship between poultry biosecurity assessments and Escherichia coli prevalence in poultry farms - Zaki, Mahmoud S.; Fahmy, Hanan A.; Khedr, Mariam H.A.; Goha, Mai A.A.; Attia, Amira S.A. (Journal of Advanced Veterinary Research, 2024)
A crucial first step in preventing the introduction and spread of harmful microorganisms in poultry farms is biosecurity. The objectives of this investigation were to assess biosecurity measures and the prevalence of different E. coli species in commercial chicken farms in Sharkia province, Egypt. Sensitivity of E. coli strains was identified, and their susceptibility to antibiotics and disinfection was evaluated as well. Four farms provided 21 samples each, for a total of 84 samples. Three samples of each were collected for water, feed, litter, cloaca, wall, hand, and foot boots. All the studied farms obtained a "poor biosecurity" grade, meaning that their overall biosecurity score, which is comprised of 40% external and 36.54% internal biosecurity, was less than 50%. Escherichia coli species were found in 79.76% of the samples. It was isolated from water, feed, litter,Â cloaca, walls, hands, and foot boots with percentages of 91.6; 83.3; 91.6; 100; 58.3; 58.3 and 75%, respectively. Biosecurity level had significant negative correlations with the isolated E. coil species. Escherichia coli O119 was the most common serotype in litter and the cloaca, while E. coli O1 was the most prevalent serotype in walls and hands. Additionally, serotypes for E. coli O26, O159, O128 and O78 were included. According to the patterns of antibiotic sensitivity, amikacin, nitrofurantoin, gentamycin, and levofloxacin showed intermediate sensitivity, whereas E. coli O119 bacteria were highly sensitive to ciprofloxacin. In the absence and presence of organic matter, Virocid, Cid 2000 and finally Virkon S were the most efficient against E. coli O119. According to this study, there were differences in the investigated farms’ biosecurity levels in relation to the occurrence of Escherichia coli. To reduce the introduction and persistence of E. coli in poultry farms, several biosecurity practices and management, including stringent cleaning and disinfection measures should be applied.